Dry-printed carbon nanotube film based electrochemical immunosensor for total testosterone detection - Narender Kumar Joon; Jane Besong-Ndika; Elisa Mikkonen; Ville Rajala; Samuel Dulay; Ilkka Varjos (Biosensors and Bioelectronics: X)
Testosterone (TST), a critical hormone for male health, requires precise monitoring due to the significant adverse effects of both deficiency and excess, including reproductive dysfunction, mood alterations, and metabolic imbalances. This study reports a novel electrochemical biosensor designed for rapid and sensitive point-of-care (POC) detection of total TST in serum samples. The sensing platform utilizes a cost-effective, roll-to-roll processed carbon nanotube (CNT) film as a scaffold. To create the biorecognition layer, bovine serum albumin-testosterone conjugate (BSA TST) was uniformly immobilized into the CNT film using an automated liquid dispensing system, enabling high-throughput and reproducible sensor fabrication. The biosensor employs a competitive immunoassay principle, where TST in the sample competes with immobilized BSA TST for the binding sites of antibody against TST horse-radish peroxidase conjugate (AbHRP). Amperometry at −0.2 V vs. Ag/AgCl ink was used to monitor affinity reaction upon addition of H2O2 with 3,3′,5,5′-Tetramethylbenzidine (TMB) redox mediator yielding a dynamic range of 82–1080 ng/dL. Limit of detection (LOD) and limit of quantification (LOQ) of 12.7 and 82 ng/dL were achieved respectively. Validation in spiked human serum demonstrated excellent performance, with quantifiable results aligning well with the established physiological range of TST in healthy males (186–1180 ng/dL), highlighting the potential of this biosensor for clinical applications.